Engajamento de stakeholders: indicações geográficas dormentes à luz da teoria - Malaguti, Jane Mary Albinati (2023)
This thesis aimed to understand why some geographical indications (GIs), which obtain their registrations with the INPI, do not evolve towards achieving the objectives of the stakeholders who were involved in obtaining the GI registration. This understanding is sought using Stakeholder Theory as a theoretical lens, in particular the construct of stakeholder engagement. To achieve the objective of the thesis, the strategy of a single case study of a GI was used as a methodology, which was considered an extreme case among those that did not achieve these objectives. Following precedent, we refer to this extreme case as a dormant GI. Extreme cases facilitate the identification and understanding of the reasons why the phenomenon under analysis occurs. The result of the analysis suggests that the reason why the GI is dormant is that the stakeholder engagement process, recommended by the literature to achieve good results in situations involving stakeholders, was not followed. A contribution of this thesis to theory is the expansion of the external validity of the stakeholder engagement construct, through the suggestion that it contributes to the understanding of phenomena that occur in contexts other than business ones. The thesis also relates aspects of stakeholder engagement with its impacts in a specific context. The use of the construct in specific contexts, especially in countries with emerging economies, is a gap indicated in the literature. From a practical point of view, the thesis suggests that managers, who in the case of GIs are referred to as procedural substitutes (PSs), should pay attention to the stakeholder engagement process. The thesis also suggests that organizations involved with the registration of GIs should pay attention to verifying the conditions of procedural substitutes to carry out the activities included in the stakeholder engagement process. From a practical point of view, the thesis also proposes guidelines for PSs, organizations and involved stakeholders to follow in order to avoid inactive GIs. Finally, the thesis indicates paths for research to broaden the understanding of how GIs can better achieve their objectives and make the social contributions expected of them. It suggests that expanding the use of the stakeholder engagement construct, which until now was not being used in the context of GIs, may be useful for this expansion.